An invitro study on the oxytocic effects of manihot grahamii extracts (matambula Leaves) in the augmentation of uterine contractions - Shitindi, Martha (Lusaka: University of Zambia , School of Medicine, 2016)
Manihot grahamii is a herb that is used by pregnant women in the communities to assist in acceleration of labor. In view of its uterotonic action; the mechanism underlying plant's effect on uterine contraction was investigated in this study. The results proved that manihout grahami leaves has uterotonic properties.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Uterus, Pregnant; Labor (Obstetrics)--Complications.